Analysis of the Application of Differentiated Learning in Class V of SDN 2 Sindue Tobata - Fatul Alya; Herlina Herlina; Asriani Asriani; Zulnuraini Zulnuraini; Putriwanti Putriwanti (FKIP - Universitas Riau, 2026)
Differentiated learning is a key approach in the Independent Curriculum that aims to accommodate students' diverse learning needs. This study aimed to analyze the implementation of differentiated learning in Grade V of SDN 2 Sindue Tobata. A qualitative descriptive approach was employed involving one classroom teacher and Grade V students. Data were collected through observations, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing. The findings showed that differentiated learning was implemented through diagnostic assessments, flexible learning activities, group discussions, student presentations, posters, and worksheets. These strategies encouraged active student participation and created a more student-centered learning environment. However, the implementation had not been fully optimized because differentiation was still mainly limited to teaching methods and learning media, while instruction based on students' readiness, interests, and learning profiles had not been consistently applied. Teachers also faced challenges related to limited instructional time, classroom management, and the preparation of differentiated learning materials. The study concludes that differentiated learning has the potential to improve the quality of classroom instruction, but continuous teacher support and professional development are needed to optimize its implementation in elementary schools.